Pengaruh Pemberian Sirup Bit Merah (Beta Vulgaris L) Terhadap Peningkatan Kadar Hemoglobin Pada Remaja Puteri Dengan Anemia - Dewita, Dewita; Putri, Selvia Zuhra; Madeni, Barirah (LPPM Institut Pendidikan Nusantara Global, 2025)
Background: Anemia in adolescents aged 15-24 years is 32% and it is estimated that 3 out of 10 people suffer from anemia. Several studies have been carried out, cases of anemia in young women are still high, this occurs due to lack of compliance with taking blood supplement tablets. The incidence of anemia in adolescent girls is around 12.1 million people due to not consuming Fe tablets. Research method: This research design uses a Quasi experimental design with pre and post test only with control group. This research was to determine the effect of giving red beet syrup and fe tablets to anemic adolescent girls in the Langsa City area. The research period was from August to September 2023. The total research sample was 30 D3 midwifery students who met the inclusion criteria and were willing to be respondents and did not suffer from chronic diseases. The research instrument used was a questionnaire. Results: The results of the Mann Witney Test showed a value of p = 0.000 < 0.05, which means there was a significant effect between the treatment group given red beet syrup and the control group. Based on the table above, it is known that in the Fe tablet group the average difference in hemoglobin increase was 8.10. In the Fe tablet and beetroot groups, the average difference in hemoglobin increase was 22.90 and the sig value was 0.000. Conclusion: based on the research results, it can be concluded that the group that gave 250 ml of red beet syrup (Beta vulgaris L) and fe tablets for 7 days proved to be more effective in increasing hemoglobin levels in adolescent girls with anemia.